Ink for insulator film formation, insulator film, and manufacturing method of insulator film
By forming a multi-layer dense layer of insulating film on the substrate, using paints of metal alkoxide compounds and oxide nanoparticles combined with light treatment, the problem of insufficient transparency and voltage tolerance of insulating films in the thickness range in the prior art is solved, and the insulating film manufacturing of high-voltage electronic equipment is realized.
Patent Information
- Application Number
- JP2023123783
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art is difficult to form an insulating film with high transparency and high voltage in the thickness range of 300 nm to 20 μm, and the existing methods are costly and inefficient, making it difficult to meet the needs of high voltage electronic equipment.
Using a coating containing metal alkoxide compound and oxide nanoparticles, a multi-layer dense layer is formed on the substrate by a light-assisted chemical solution deposition method, and the density and voltage tolerance of the film are improved by light treatment.
The insulating film in the thickness range of 300 nm to 20 μm has a voltage bearing capacity of more than 1 kV and an electric field strength of 2.6 MV/cm, which is suitable for high reliability semiconductor manufacturing equipment and high safety power electronic equipment.
Smart Images

Figure 2025019894000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an insulating film-forming ink, an insulating film, and a method for producing an insulating film. [Background technology]
[0002] Yttria (Y2O3) and alumina (Al2O3) (hereinafter referred to as "insulating oxides") are used as insulating films (insulating layers) in various applications. The main applications of the insulating oxides include, for example, the following: The insulating oxide is used in electronic devices as an insulating film for semiconductor devices and high-performance electronic devices, and an insulating layer for gate stacks. Insulating films and insulating layers made of the insulating oxide are known to have high insulating performance. The insulating oxide is also coated on the surfaces of optical lenses and mirrors as an optical coating agent. This coating improves the durability and optical performance of the optical lenses and mirrors. The insulating oxide has a high withstand voltage (or dielectric breakdown field strength), and is therefore particularly effective in high-voltage electronic devices such as semiconductor manufacturing equipment, power electronics devices, high-voltage transistors, and power conversion equipment. In other words, the insulating oxide makes a significant contribution to improving the safety and reliability of the equipment.
[0003] In insulating films made of the insulating oxides, there is a trade-off between optical properties such as transparency and high withstand voltage. For example, when attempting to obtain a high withstand voltage of 1 kV or more, transparency may be lost if the insulating film is made 10 μm to 20 μm thick. Therefore, achieving both transparency and high withstand voltage is one of the challenges for insulating films. There are also few options for film-forming processes that can obtain insulating films with high withstand voltages at a thickness of 300 nm to 20 μm, and there is a need to develop a film-forming process that can obtain insulating films with sufficient withstand voltage in this film thickness range. Figure 1 shows the dielectric breakdown field (E BV The relationship between the E (MV / cm) and the film thickness (μm) is shown. BV =kt-n (k=1.75, n=0.351). The expected value of the dielectric breakdown field generally falls within the gray area shown in Figure 1, which indicates the expected performance value. Although several methods have been attempted to form yttria films, there have been few reports on yttria films with thicknesses in the range of 300 nm to 20 μm. Many applications of yttria films include those in which it is important to obtain a high dielectric breakdown field and a high withstand voltage. Yttria films are particularly in demand for power conversion devices and semiconductor manufacturing devices, which require high withstand voltages.
[0004] It is known that the crystal quality, which determines the insulating properties of an insulating film, has a large effect on the properties of the insulating film. In order to obtain crystals of a quality effective for insulation, precise control of the growth conditions is important. In particular, to obtain an insulating film with high dielectric breakdown resistance, it is important to control the crystal grain shape and grain boundaries that compose the insulating film, and high control is required from the film-forming raw materials. In addition, there are issues in terms of film-forming costs when producing insulating films. Generally, when forming a large insulating film, issues may arise in the deposition-based process that requires a large vacuum chamber. In contrast, a method of forming an insulating film by applying a chemical solution to a substrate is attracting attention as a method that does not require a large vacuum chamber. In the method of forming a film using a chemical solution, a solution (or a dispersion of particles) that is the raw material of the target material is applied to a substrate to form a coating film, and the substrate on which the coating film has been formed is heated and fired to form a ceramic film that will become an insulating film.
[0005] In addition, when the low heat resistance of the substrate is a problem, a process of irradiating light onto an insulating film is known to densify or crystallize the insulating film. The deposition method of a crystalline ceramic film by printing generally requires a high-temperature process of 500°C or more. Therefore, the use of laser or flash lamp light is known as an attempt to avoid high-temperature treatment for the crystallization of ceramics and enable a low-temperature process (see, for example, Patent Document 1, Patent Document 2, and Non-Patent Document 1). After the substrate coated with the raw material solution of the ceramic film is heated and dried, it can be crystallized at room temperature by irradiation with an ultraviolet pulse laser such as an excimer laser. For example, Patent Document 3 describes a film formation method in which a precursor film of an yttria film formed by a coating method is crystallized by light irradiation. In addition, Patent Document 1 describes a low-temperature crystal growth method of an oxide film such as an yttria film by a process of coating a nanoparticle dispersion onto a substrate and irradiating it with light. The method of densifying or crystallizing a film by light irradiation based on the coating method is called Photo-assisted Chemical Solution Deposition (PCSD method).
[0006] However, it is not easy to form an insulating film that fully exhibits high withstand voltage (or high dielectric breakdown field strength) by the coating method due to the influence of micropores and cracks. The coating method and other film formation processes generally follow the E BV =kt -nIt has not been possible to form an insulating film that exceeds the expected performance value estimated from the above (k=1.75, n=0.351). In order to obtain a high withstand voltage (>1 kV), it is necessary to form an insulating film with a thickness of 10 μm to 20 μm or more by a thick film deposition method such as a plasma spray method. However, it is very difficult to form an insulating film that can withstand a high voltage of 1 kV or more with a thickness of less than 20 μm. In Patent Document 1 and Patent Document 3, there is no mention of achieving a high withstand voltage (or high dielectric breakdown field strength). The median expected value of the dielectric breakdown field strength at 300 nm as understood from FIG. 1 is 2.6 MV / cm, and it is of great value to form an insulating film that achieves a high withstand voltage (>1 kV) or a high dielectric breakdown field strength (>2.6 MV / cm) that exceeds this value, especially in the film thickness range of 300 nm to 20 μm. For example, the withstand voltage of the yttria film manufactured by the thermal spray method shown in Patent Document 4 reaches 4.4 kV. However, the dielectric breakdown field strength is 0.15 MV / cm, and although the effect is exhibited in a region where the film thickness is thicker than 20 μm, high characteristics are not shown in a region where the film thickness is thinner than 20 μm. On the other hand, as described in Non-Patent Document 2, it is known that the atomic layer deposition (ALD) method can form an yttria film with a high dielectric breakdown field strength in a film thickness region of less than 300 nm. However, it is known that the ALD method is not suitable for manufacturing thick films, and is not suitable for manufacturing insulating films with good characteristics when the film thickness is 300 nm or more. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 5697085 [Patent Document 2] Patent No. 6529023 [Patent Document 3] Patent No. 4258536 [Patent Document 4] Patent No. 4006535 [Non-patent literature]
[0008] [Non-Patent Document 1] Tomohiko Nakajima, Tetsuo Tsuchiya, “Ultrathin Highly Flexible Featherweight Ceramic Temperature Sensor Arrays”, ACS Appl. Mater. Interfaces 2020,12,36600-36608. [Non-Patent Document 2] Philippe de Rouffignac, Jin-Seong Park, Roy G. Gordon, “Atomic Layer Deposition of Y2O3 Thin Films from Yttrium Tris(N,N-diisopropylacetamidinate) and Water”, Chem. Mater.17(2005)4808-4814. Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention has been made in consideration of the above circumstances, and has an object to provide an insulating film-forming ink, an insulating film, and a method for manufacturing an insulating film, which are capable of forming an insulating film having a film thickness of 300 nm to 20 μm and high withstand voltage or high dielectric breakdown field strength. [Means for solving the problem]
[0010] The present inventors have discovered a film-forming process that achieves the above characteristics by applying a nanoparticle dispersion capable of forming a coating-type insulating film that achieves a high withstand voltage (>1 kV) or a high dielectric breakdown field strength (>2.6 MV / cm) to a coating material and a substrate, forming a dried precursor film, and irradiating light. The present invention provides an insulating film formation method that achieves a high withstand voltage or a high dielectric breakdown field strength by irradiating a pulsed light to a solution containing metal ion species that also constitute an insulating oxide and an insulating film-forming ink that is monodispersed in a solvent, and a precursor film that is coated and formed on a substrate using the insulating film-forming ink, with the aim of effectively bonding between minute insulating oxide nanoparticles of 30 nm or less.
[0011] The present invention has the following aspects. [1] An insulating film forming ink comprising a solvent, an organometallic compound or a metal alkoxide, and oxide nanoparticles, the organometallic compound or the metal alkoxide contains a metal component constituting an insulating oxide material, the oxide nanoparticles are composed of crystallites of the insulating oxide material having a crystallite size of 0.5 nm or more and 15 nm or less; The oxide nanoparticles have an average primary particle diameter of 30 nm or less, The content of the oxide nanoparticles is 0.5% by mass or more and 10% by mass or less, The ink for forming an insulating film, wherein the content of the organometallic compound or the metal alkoxide is 5% by mass or more and 25% by mass or less. [2] further comprising a nanoparticle dispersant; The ink for forming an insulating film according to [1], wherein the content of the nanoparticle dispersant is 10 mass % or less. [3] The oxide nanoparticles are represented by the general formula AO x (wherein A is one or more elements selected from Sc, Y, group 3 elements of lanthanides, Ti, Zr, Hf, group 4 elements, Nb, Ta, Si, and Al, and x is a value that matches the valence of A and maintains electrical neutrality, but slight oxygen non-stoichiometry is allowed.) [4] The organometallic compound or the metal alkoxide is represented by the general formula M m R n (wherein M is at least one element selected from Sc, Y, Group 3 elements of the lanthanoids, Group 4 elements of Ti, Zr, Hf, Nb, Ta, Si, and Al; R is at least one selected from an alkyl group having 1 to 4 carbon atoms, a carboxyl group having 1 to 4 carbon atoms, and a carbonyl group; and m and n are integers), or is a β-diketonato or a long-chain alkoxide having 6 or more carbon atoms. The ink for forming an insulating film according to any one of [1] to [3]. [5] When the organometallic compound or the metal alkoxide is an organometallic compound, the solvent is a mixed solvent of b% by volume of an aromatic hydrocarbon and 100 - b% by volume of an alcohol (10 < b < 90). The ink for forming an insulating film according to any one of [1] to [4]. [6] The organometallic compound or the metal alkoxide is a 2-ethylhexanoate. The ink for forming an insulating film according to any one of [1] to [5]. [7] The aromatic hydrocarbon is toluene or xylene. The ink for forming an insulating film according to [5]. [8] The alcohol is 1-butanol or isopropanol. The ink for forming an insulating film according to [5]. [9] A is Y. The ink for forming an insulating film according to [3].
[10] M is Y. The ink for forming an insulating film according to [4].
[11] An insulating film composed of Y2O3 (AO x : A = Y, x = 1.5) formed on a substrate, having a laminated structure in which a plurality of dense layers having a thickness of 30 nm or more and 300 nm or less are laminated, and the thickness of the laminated structure is 300 nm or more and 20 μm or less, the dense layer is composed of crystallites having a crystallite size of the Y2O3 of 0.5 nm or more and 15 nm or less, the layers between the laminated structures are connected by layers having the same composition among the dense layers, and having a breakdown voltage of 1 kV or more or an electric field strength at breakdown of 2.6 MV / cm or more. The insulating film.
[12] A first step of applying an insulating film forming ink according to any one of [1] to
[10] onto a substrate to form a precursor film on the substrate; a second step of drying the precursor film at a temperature of 100° C. or more and 400° C. or less; and a third step of irradiating the dried precursor film with a solid pulse laser having a wavelength of 266 nm or more and 355 nm or less, an excimer laser having a wavelength of 193 nm or more and 308 nm or less, or a flash lamp to form an insulating film.
[13] The first step, the second step, and the third step are repeated in this order to obtain Y2O3(AO x : A=Y, x=1.5), forming a laminated structure in which multiple dense layers having a thickness of 30 nm to 300 nm are laminated. Effect of the Invention
[0012] According to the present invention, it is possible to obtain an insulating film having a superior thickness in the range of 300 nm to 20 μm. The present invention includes an insulating film forming ink for coating and forming the insulating film, an insulating film capable of realizing a withstand voltage of 1 kV or more or a dielectric breakdown field strength of 2.6 MV / cm or more, and a method for manufacturing an insulating film capable of forming an effective insulating film using the insulating film forming ink. If a high withstand voltage or a high dielectric breakdown field strength can be obtained in the thickness range of 300 nm to 20 μm, it will be possible to construct a highly reliable semiconductor manufacturing apparatus and to manufacture safe power electronics devices, high voltage transistors, power conversion devices, etc. [Brief description of the drawings]
[0013] [Figure 1]FIG. 1 shows the film thickness dependence of the dielectric breakdown field strength of yttria films prepared by various methods (abbreviations in the figure: AD: Aerosol Deposition method, ALD: Atomic Layer Deposition method, CSD: Chemical Solution Deposition method, CVD: Chemical Vapor Deposition method, EBE: Electron Beam Evaporation method, IBAD: Ion-Beam Assist Deposition method, MBE: Molecular Beam Epitaxy method, PS: Plasma Spray method, PLD: Pulsed Laser Deposition method, SP: Sputtering method, PCSD: Photo-assisted Chemical Solution Deposition method (values obtained in the present invention, Examples 1 and 2)). [Diagram 2] FIG. 1 is a conceptual diagram of crystal grains and crystallites related to nanoparticles. [Diagram 3] FIG. 2 is a conceptual diagram showing a cross section in the thickness direction of a laminated structure obtained by applying an insulating film forming ink multiple times. [Figure 4] FIG. 2 is a diagram showing the nanoparticle size distribution of the oxide Y2O3 nanoparticles contained in the Y2O3 ink C1 for forming an edge film obtained in Example 1. [Diagram 5] FIG. 1 shows X-ray diffraction patterns of the Y2O3 films obtained in Example 1 and Comparative Example 6. [Figure 6] FIG. 2 shows a cross-sectional TEM image of the Y2O3 film obtained in Example 1 and a lattice image of the dense layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] An embodiment of the ink for forming an insulating film, the insulating film, and the method for producing an insulating film of the present invention will be described. It should be noted that the present embodiment is specifically described to allow a better understanding of the gist of the invention, and does not limit the present invention unless otherwise specified.
[0015] [Insulating film forming ink] An ink for forming an insulating film according to one embodiment of the present invention contains a solvent, an organometallic compound or a metal alkoxide, and oxide nanoparticles.
[0016] "solvent" The solvent is not particularly limited as long as it can dissolve the organometallic compound or metal alkoxide and disperse the oxide nanoparticles. Examples of such solvents include aromatic hydrocarbons such as toluene, xylene, ethylbenzene, styrene, and pyridine, and alcohols such as 1-butanol, isopropanol, ethanol, methanol, ethylene glycol, and normal propyl alcohol. These solvents may be used alone or in combination of two or more. The aromatic hydrocarbon is preferably toluene or xylene from the viewpoints of solubility of the organometallic compound, adjustment of ink viscosity, and wettability to the substrate. When a metal alkoxide is used, the alcohol is preferably methanol, 2-methoxyethanol, or ethanol from the viewpoint of solubility, and when an organometallic compound is used, 1-butanol or isopropanol is preferable from the viewpoint of solubility, miscibility with toluene or xylene, and ink viscosity adjustment. In addition, many organometallic compounds are sold in the form of a diluted solution with a toluene solvent or a xylene solvent, making them easy to use. In addition, metal alkoxides are generally dissolved in an ethanol solvent, making them easy to use.
[0017] In order to adjust the viscosity of the ink for forming an insulating film, as the solvent, a mixed solvent of an aromatic hydrocarbon and an alcohol is effective. This mixed solvent exerts an effect on adjusting the viscosity of the ink for forming an insulating film and the wettability when applying the ink for forming an insulating film to a substrate. When the organometallic compound or metal alkoxide is the organometallic compound described later, the solvent is preferably a mixed solvent of b% by volume of an aromatic hydrocarbon and 100 - b% by volume of an alcohol (10 < b < 90). b is preferably more than 10 and less than 90, more preferably more than 15 and less than 50, and even more preferably more than 20 and less than 35. When b is less than or equal to the lower limit value, the dispersibility of the oxide nanoparticles deteriorates and aggregation is likely to occur, making it difficult to prepare a monodisperse dispersion. When b is greater than or equal to the upper limit value, the ink viscosity becomes excessive, making handling difficult, and the wettability to the substrate deteriorates, and it may be impossible to obtain a high-quality insulating film.
[0018] When the solvent is a mixed solvent of an aromatic hydrocarbon and an alcohol, a mixed solvent containing toluene and 1-butanol, a mixed solvent containing toluene and isopropanol, and a mixed solvent containing xylene and 1-butanol are preferred.
[0019] The content of the solvent in the ink for forming an insulating film of the present embodiment is preferably 65% by mass or more and 94.5% by mass or less, more preferably 70% by mass or more and 93% by mass or less, and even more preferably 78% by mass or more and 90% by mass or less with respect to the total mass (100% by mass) of the ink for forming an insulating film. When the content of the solvent is less than the lower limit value, the viscosity of the ink becomes high, making it difficult to uniformly coat a thin film and difficult to form a dense layer. When the content of the solvent exceeds the upper limit value, the active ingredient for forming the insulating film decreases, making it difficult to increase the film thickness.
[0020] "Organometallic compound or metal alkoxide" The organometallic compound or metal alkoxide is a material for the insulating film. The organometallic compound or metal alkoxide contains a metal component constituting an insulator oxide material for forming the insulating film. Examples of insulating oxide materials include Y2O3, Al2O3, TiO2, ZrO2, HfO2, Nb2O5, Ta2O5, SiO2, and Sc2O3.
[0021] The organometallic compounds or metal alkoxides are represented by the general formula M m R n (wherein M is one or more elements selected from Sc, Y, group 3 elements of the lanthanides, group 4 elements of Ti, Zr, Hf, Nb, Ta, Si, and Al, and R is an alkyl group having 1 to 4 carbon atoms (CH3, C2H5, C3H7, C4H9), a carboxyl group having 1 to 4 carbon atoms (CH3COO - , C2H5COO - , C3H7COO - , C4H9COO - ) and at least one selected from the group consisting of a carbonyl group, m and n being integers. ) or a β-diketonate or a long-chain alkoxide having 6 or more carbon atoms. m R n In terms of oxide materials that exhibit high withstand voltage, M is preferably Y (yttrium), Al (aluminum), or Si (silicon).
[0022] The above general formula M m R n As the organometallic compound or metal alkoxide represented by the formula (I), for example, 2-ethylhexanoate, acetylacetone complex, naphthenate, acetate, ethoxide, isopropoxide, etc. are preferable. Among these, 2-ethylhexanoate is more preferable from the viewpoint of solubility when a non-polar solvent is used. In the ink for forming the insulating film of this embodiment, examples of the 2-ethylhexanoate include yttrium 2-ethylhexanoate and aluminum 2-ethylhexanoate.
[0023] The content of the organometallic compound or metal alkoxide in the insulating film forming ink of this embodiment is 5% by mass or more and 25% by mass or less, preferably 8% by mass or more and 20% by mass or less, and more preferably 10% by mass or more and 16% by mass or less, based on the total mass (100% by mass) of the insulating film forming ink. If the content of the organometallic compound or metal alkoxide is less than the lower limit, the bond between the oxide nanoparticles becomes insufficient, and the function as an insulating film is reduced. If the content of the organometallic compound or metal alkoxide exceeds the upper limit, the viscosity of the ink increases, making it difficult to handle or causing cracks after application, and similarly reducing the function as an insulating film.
[0024] "Oxide nanoparticles" The oxide nanoparticles are insulating film materials, similar to organometallic compounds or metal alkoxides. The oxide nanoparticles are composed of crystallites of the insulating oxide material, the crystallite size of which is 0.5 nm to 15 nm. The crystallite size of the insulating oxide material is preferably 0.5 nm to 10 nm, more preferably 0.5 nm to 8 nm. If the crystallite size is less than the lower limit, the insulating properties as a material property are reduced. If the crystallite size exceeds the upper limit, the formation of a dense layer becomes insufficient, and the function as an insulating film is reduced.
[0025] The crystallite size of insulating oxide materials can be measured by analysis using the Scherrer equation for X-ray diffraction peaks (D=K λ / (βcosθ), where D is the crystallite size, K is the Scherrer constant, λ is the X-ray wavelength, and β is the half-width at the peak position 2θ) or by observation using transmission electron microscope images.
[0026] The oxide nanoparticles have an average primary particle diameter of 30 nm or less, preferably 5 nm to 20 nm, and more preferably 5 nm to 15 nm. Within the above range, when an insulating film is formed using oxide nanoparticles, the oxide nanoparticles form a dense layer and numerous crystal grain boundaries. As a result, unnecessary electric field concentration during voltage application is avoided by densification, and by forming a dense layer with fine oxide nanoparticles, it is considered that a phase with lower resistance (semiconductor behavior) than the inside of the crystal is generated at the nanoparticle crystallite interface due to the high degree of crystal imperfection, and it is considered that the free electrons generated during high voltage application are absorbed and avalanche breakdown is suppressed. It is considered that by generating numerous crystal grain boundaries, the progress of avalanche path generation is suppressed, resulting in high electric field strength.
[0027] In the ink for forming an insulating film, dissolving an organometallic compound or a metal alkoxide in a solvent is essential for promoting bonding between oxide nanoparticles and forming a dense layer when forming an insulating film. If the ink for forming an insulating film contains only an organometallic compound or a metal alkoxide, increasing the thickness of the insulating film may cause large cracks to form in the insulating film. Therefore, it is also important that the ink for forming an insulating film contains oxide nanoparticles. That is, in the ink for forming an insulating film of this embodiment, mixing oxide nanoparticles with an organometallic compound or a metal alkoxide is an essential condition.
[0028] The primary particle size of oxide nanoparticles can be measured by a method in which the solvent is removed from a dispersion liquid containing oxide nanoparticles by evaporation or the like, and then the remaining particles are confirmed by a magnified photograph taken with an electron microscope, or by a method in which the diameter of the primary particles is measured using an optical particle size distribution analyzer that uses laser diffraction / scattering or the like.
[0029] Oxide nanoparticles are represented by the general formula AO x(wherein A is one or more elements selected from Sc, Y, group 3 elements of lanthanoids, Ti, Zr, Hf group 4 elements, Nb, Ta, Si, and Al, and x is a value that matches the valence of A and maintains electrical neutrality, but slight oxygen non-stoichiometry is permitted.) x In terms of oxide materials that exhibit high withstand voltage, A is preferably Y (yttrium), Al (aluminum), or Si (silicon).
[0030] The above general formula AO x As the oxide nanoparticles represented by the formula (I), for example, YO x , AlO x , TiO x , ZrO x , HfO x , NbO x , TaO x , SiO x , ScO x Among these, from the viewpoint of oxide materials that exhibit high withstand voltage, YO x , AlO x , SiO x It is preferable that:
[0031] The content of oxide nanoparticles in the ink for forming an insulating film of this embodiment is 0.5% by mass or more and 10% by mass or less, preferably 0.6% by mass or more and 8.0% by mass or less, and more preferably 0.7% by mass or more and 5.0% by mass or less, based on the total mass (100% by mass) of the ink for forming an insulating film. If the content of oxide nanoparticles is less than the lower limit, the film thickness of each coating becomes extremely thin. If the content of oxide nanoparticles exceeds the upper limit, the viscosity of the ink becomes excessive, causing abnormalities in the coating properties and cracks during drying.
[0032] "Nanoparticle Dispersant" The insulating film forming ink of this embodiment preferably further contains a nanoparticle dispersant. The nanoparticle dispersant is for dispersing oxide nanoparticles, and organometallic compounds or metal alkoxides in a solvent.
[0033] Examples of nanoparticle dispersants include nonionic surfactants, ammonium polycarboxylates, ionic surfactants, etc. When a large amount of nonpolar solvent is contained, it is preferable to use nonionic surfactants among these, but it is preferable to select a dispersant from the viewpoint of interaction with solvent molecules.
[0034] The content of the nanoparticle dispersant in the insulating film forming ink of this embodiment is preferably 10% by mass or less, more preferably 6.0% by mass or less, and even more preferably 3.0% by mass or less, based on the total mass (100% by mass) of the insulating film forming ink. If the content of the nanoparticle dispersant exceeds the upper limit, it may become a factor that inhibits densification during drying. The lower limit of the content of the nanoparticle dispersant in the insulating film forming ink of this embodiment is preferably 0.1 mass % or more. If the content is below this limit, it becomes difficult to obtain a monodisperse dispersion.
[0035] According to the ink for forming an insulating film of this embodiment, an insulating film having a withstand voltage of 1 kV or more or a dielectric breakdown field strength of 2.6 MV / cm or more can be formed. In the ink for forming an insulating film of this embodiment, the metal component constituting the insulating oxide material is an organometallic compound or a metal alkoxide dissolved in a solvent. The organometallic compound or the metal alkoxide promotes bonding between oxide nanoparticles when forming an insulating film. When the organic component of the organometallic compound or the metal alkoxide is dried and decomposed, the remaining metal ion species changes to an oxide, which plays a role in bonding between the oxide nanoparticles that have been mixed in advance, and is therefore indispensable for forming a dense layer. On the other hand, since the organometallic compound or the metal alkoxide alone can also cause large cracks to form when the thickness of the insulating film is increased, it is also important to introduce oxide nanoparticles, and mixing the oxide nanoparticles with the organometallic compound or the metal alkoxide is an essential condition. In particular, the crystallite diameter of the material constituting the insulating film to be finally formed must be very small, between 0.5 nm and 15 nm, and it is necessary to use oxide nanoparticles that are previously suppressed to this crystallite diameter.
[0036] [Method of manufacturing the ink for forming insulating film] The ink for forming an insulating film of this embodiment can be produced by a wet method using a ball mill. In order to form a dense layer, it is necessary that the oxide nanoparticles are monodispersed in the ink for forming the insulating film. Therefore, it is preferable to mix a solvent, an organometallic compound or a metal alkoxide, and oxide nanoparticles, as well as a commonly used dispersant, and wet-grind and mix these materials. In order to avoid the inclusion of particles with a particle size of more than 100 nm, such as primary aggregates and secondary aggregates, the dispersion obtained by wet grinding can be left to stand, and then the supernatant in which the monodispersed particles are dispersed can be separated to remove the precipitated particles, thereby obtaining a monodispersed liquid. For example, when forming an yttria film (Y2O3), Y2O3 nanoparticles with a particle size of 5 nm to 15 nm can be added to a mixed solvent of toluene and 1-butanol in which yttrium 2-ethylhexanoate is dissolved, and a nanoparticle dispersion can be obtained by a ball mill, and then the supernatant can be separated to obtain an ink for forming an insulating film in which Y2O3 nanoparticles with a particle size of 10 nm are monodispersed. The monodispersed particle size in this case refers to the geometric particle, and as shown in Figure 2, it does not matter how many crystallites (single crystal nuclei) are composed in a single particle.
[0037] [Insulating film] The insulating film according to one embodiment of the present invention is a Y2O3(AO) film formed on a substrate. x : A=Y, x=1.5). The insulating film of this embodiment has a multi-layer structure in which multiple dense layers, each having a thickness of 30 nm or more and 300 nm or less, are stacked, and the thickness of the multi-layer structure is 300 nm or more and 20 μm or less. That is, the insulating film of this embodiment has a multi-layer structure in which multiple dense layers, each having a thickness of 30 nm or more and 300 nm or less, are stacked, and the total thickness of the multi-layer structure is 300 nm or more and 20 μm or less.
[0038] The dense layer is composed of Y2O3 crystallites having a crystallite size of 0.5 nm to 15 nm. The crystallite size of Y2O3 is preferably 0.5 nm to 12 nm, more preferably 0.5 nm to 8 nm. If the crystallite size of Y2O3 is less than the lower limit, the insulating properties as a material property are reduced. If the crystallite size of Y2O3 exceeds the upper limit, the dense layer is not sufficiently formed, and the function as an insulating film is reduced.
[0039] The crystallite size of Y2O3 can be measured by analysis using the Scherrer equation for X-ray diffraction peaks or by observation using a transmission electron microscope image.
[0040] The thickness of the dense layer is 30 nm to 300 nm, preferably 40 nm to 250 nm, and more preferably 50 nm to 200 nm. If the thickness of the dense layer is less than the lower limit, it becomes difficult to ensure the structure of the dense layer due to the film thickness fluctuation during film formation. If the thickness of the dense layer exceeds the upper limit, the amount of oxide nanoparticles contained in the ink is considered to be excessive, which may cause deterioration of the film quality, such as the occurrence of cracks.
[0041] The number of stacked dense layers is not particularly limited as long as the thickness of the stacked structure is within a predetermined range.
[0042] The thickness of the laminated structure is 300 nm to 20 μm, preferably 500 nm to 10 μm, and more preferably 800 nm to 2 μm. If the thickness of the laminated structure is less than the lower limit, there is a concern that dielectric breakdown may occur due to the formation of micropores during film formation. If the thickness of the laminated structure exceeds the upper limit, a considerable number of coating steps are required, making film formation impractical and increasing the superiority of other methods such as spray coating.
[0043] The layers in the laminated structure, i.e., the dense layers, are connected by layers of the same composition.
[0044] The insulating film of this embodiment has a withstand voltage of 1 kV or more or a dielectric breakdown field strength of 2.6 MV / cm or more. The withstand voltage of the insulating film of this embodiment can be measured by applying a voltage between the lower electrode and the upper electrode and increasing the voltage until dielectric breakdown occurs. The dielectric breakdown field strength of the insulating film of this embodiment can be measured, for example, by forming an insulating film on a conductive substrate such as ITO glass, forming a film of ITO or gold on the upper part to serve as an upper electrode, and monitoring the current value while applying a voltage between the electrodes.
[0045] The insulating film of this embodiment has a withstand voltage of 1 kV or more or a dielectric breakdown field strength of 2.6 MV / cm or more, and is particularly advantageous when the thickness is 300 nm or more and 20 μm or less. If a high withstand voltage or high dielectric breakdown field strength can be obtained with a thickness of 300 nm or more and 20 μm or less, it will be possible to build highly reliable semiconductor manufacturing equipment and to manufacture safe power electronics devices, high-voltage transistors, power conversion equipment, etc.
[0046] [Method of manufacturing insulating film] A method for producing an insulating film according to one embodiment of the present invention includes a first step of applying an insulating film forming ink according to the above-described embodiment onto a substrate to form a precursor film on the substrate, a second step of drying the precursor film at a temperature of 100° C. or more and 400° C. or less, and a third step of irradiating the dried precursor film with a solid-state pulse laser having a wavelength of 266 nm or more and 355 nm or less, an excimer laser having a wavelength of 193 nm or more and 308 nm or less, or a flash lamp to form an insulating film.
[0047] The method for producing an insulating film according to the present embodiment includes repeating the first step, the second step, and the third step in this order to form a film of Y2O3(AO x : A=Y, x=1.5), and a laminate structure is formed in which a plurality of dense layers having a thickness of 30 nm or more and 300 nm or less in the above embodiment are laminated.
[0048] "First step" In the first step, the method for applying the ink for forming an insulating film onto the substrate (application method) may be a general method capable of surface application, such as spin coating, bar coating, die coating, etc. By this application method, a precursor film of the insulating film can be formed on the substrate from the ink for forming an insulating film.
[0049] "Second step" In the second step, the precursor film formed on the substrate is dried at a temperature of 100° C. to 400° C. For drying the precursor film, a hot plate, an electric furnace, lamp heating, or other means can be used.
[0050] By repeating the formation of the precursor film in the first step and the drying of the precursor film in the second step, the thickness of the laminated film consisting of a plurality of laminated precursor films is increased. Although the geometric structure of the resulting film differs depending on the composition of the ink for forming the insulating film, by repeating the first and second steps, a laminated structure in which dense layers are stacked according to the number of layers can be obtained. This laminated structure is also one of the features, and crystallites with a crystallite size of 0.5 nm to 15 nm (most of them are distributed in sizes of about 3 nm to 8 nm with a center of about 5 nm, and even if there are rare cases where crystallites larger than 15 nm are present, it is desirable that 95% by volume or more falls within the above range.) form a dense layer with a thickness of 30 nm to 300 nm, and the dense layer forms a laminated structure, and the laminated structure has a thickness of 300 nm to 20 μm, becoming an insulating film.
[0051] The layers of the obtained laminated structure are connected by dense layers of the same composition, and flat voids may occur between the laminated structures in a direction parallel to the substrate. However, since the voids are flat, when the film thickness is increased, they do not cause breakdown at low voltages due to excessive electric field concentration, and the desired high withstand voltage or high dielectric breakdown field strength is achieved. In this case, the flat voids are often 5 nm to 50 nm (often 100 nm or less at most) in the short side direction and 50 nm to 250 nm in the long side direction, and are randomly distributed between the laminated structures. A conceptual diagram of the thickness direction of the laminated structure of the insulating film is shown in Figure 3. In order for an insulating film formed using an insulating film forming ink to exhibit sufficiently high insulating properties, it is considered important to form a dense layer composed of extremely small crystallites and to form a large number of barriers (grain boundaries) that prevent electrons from penetrating when an electric field is applied. Therefore, it is considered that by using an insulating film forming ink, an insulating film with high insulating properties can be achieved even in a geometric structure other than the above. However, excessive energy input in order to densify the precursor film formed by coating must not be used, as this may increase the crystallite size more than necessary, excessively reduce the number of grain boundaries, or cause deep cracks. The crystallite size is measured using the Scherrer equation, which is expressed by the following formula (1), using an X-ray diffraction pattern. D = (K λ / βcosθ) (1) In the above formula (1), D is the crystallite diameter, K is the Scherrer constant (0.94), λ is the X-ray wavelength, and θ is the Bragg angle. The crystallite shape can also be directly observed using a transmission electron microscope.
[0052] "The third step" When forming an insulating film, after drying the precursor film in the second step, heating with a hot plate or an electric furnace can be used to densify the film, but in this embodiment, it has been found that the PCSD method using pulsed light irradiation is particularly effective. In the third step, the precursor film formed by coating on the substrate is dried at a temperature of 100°C to 400°C, and then an insulating film can be formed by irradiating a solid pulse laser with a wavelength of 266 nm to 355 nm, an excimer laser with a wavelength of 193 nm to 308 nm, or a flash lamp. It is particularly effective to perform the first and second steps and irradiate the precursor film with light for each layer. For example, to form a Y2O3 film, the substrate temperature is set to 300°C, and 3000 pulses of an excimer laser KrF laser are irradiated at a fluence of 60 mJ / cm2 to 100 mJ / cm2 to form an insulating film having a high withstand voltage or high dielectric breakdown field strength. In addition, to form the Y2O3 film, the KrF laser was used at a substrate temperature of 300°C and 30 mJ / cm 2 fluence of 1000 pulses, 80 mJ / cm 2 The fluence is 3000 pulses and two consecutive stages of irradiation are performed. The first stage of the two consecutive stages of irradiation is a pretreatment for removing residual carbon in the precursor film, and the second stage is an irradiation for increasing the bonds between nanoparticles and densifying them. When the film thickness is 1.4 μm, the withstand voltage exceeds 1.81 kV and the dielectric breakdown field strength is 12.7 MV / cm, which is an extremely high value. This is about 10 times higher than the value expected from the yttria film obtained by the conventional method shown in FIG. 1. Compared to the conventional yttria film with high crystallinity, the insulating film (yttria film) controlled to a fine crystallite diameter of this embodiment is considered to have succeeded in forming a new insulating film that goes beyond the scope of previous understanding of characteristics.
[0053] According to the method for producing an insulating film of this embodiment, an insulating film having a withstand voltage of 1 kV or more or a dielectric breakdown field strength of 2.6 MV / cm or more can be formed. In the method for producing an insulating film of this embodiment, the ink for forming an insulating film of the above-mentioned embodiment can be used to form an insulating film having a high withstand voltage or a high dielectric breakdown field strength, and it is effective to use the PCSD method to finally obtain an insulator film having a crystallite diameter of 0.5 nm to 15 nm. In addition, in the method for producing an insulating film of this embodiment, a dense layer is formed with crystallites having a crystallite diameter of 0.5 nm to 15 nm, and the dense layer forms a laminated structure with a thickness of 300 nm to 20 μm, and the layers of the laminated structure are connected by dense layers of the same composition, and it is possible to obtain a high withstand voltage or a high dielectric breakdown field strength. In order to obtain the laminated structure, the ink for forming an insulating film of the above-mentioned embodiment and the PCSD method can also be used as a film formation process. Furthermore, according to the insulating film manufacturing method of the present embodiment, it is possible to form an insulating film based on a coating method, and therefore it is expected to be applied to highly efficient manufacturing, such as reducing manufacturing costs and on-demand manufacturing. EXAMPLES
[0054] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0055] Example 1 A mixed solution was prepared by dissolving 4.0 mL of yttrium 2-ethylhexanoate solution (manufactured by Nippon Chemical Industry Co., Ltd.) and 0.3 g of dispersant SN9228 (manufactured by San Nopco Co., Ltd.) in a mixed solvent of 20 mL of toluene and 6 mL of 1-butanol. 0.8 g of Y2O3 nanoparticles (manufactured by US Research Nanomaterials) with a primary particle size of 10 nm was added to the mixed solution, which was then mixed and dispersed in a ball mill for 8 hours. After leaving the mixture to stand for 3 days, coarse precipitated particles were removed to obtain Y2O3 ink C1 for forming an insulating film.
[0056] Figure 4 shows the particle size distribution of the oxide Y2O3 nanoparticles contained in Y2O3 ink C1 for forming insulating film. When the particle size was measured using an optical particle size distribution meter using laser diffraction and scattering, it was found to be distributed in the range of 14.7 nm or less, with a median diameter of 10.7 nm in the particle number distribution, and it was confirmed that a nanoparticle dispersion with good dispersibility was obtained with no other distribution of aggregated particles.
[0057] Next, the obtained Y2O3 ink C1 for forming an insulating film was spin-coated on an ITO glass substrate at a rotation speed of 3000 rpm for 20 seconds, and it was confirmed that a precursor film could be formed with good coating properties. After the precursor film was coated, it was pre-baked at 150°C for 5 minutes and at 400°C for 10 minutes, and then irradiated with a KrF laser (pulse width 26 ns) with a wavelength of 248 nm at a substrate temperature of 300°C at 30 mJ / cm. 2 fluence of 1000 pulses, 80 mJ / cm 2 The fluence was 3000 pulses and two consecutive stages of irradiation. The process from application to laser irradiation was repeated 20 times. This resulted in the formation of a Y2O3 film.
[0058] When the X-ray diffraction pattern of the obtained Y2O3 film was confirmed, a very broad X-ray diffraction peak was confirmed, and the crystallite diameter was analyzed to be 3 nm to 12 nm by analysis using the Scherrer formula. The X-ray diffraction pattern of the Y2O3 film is shown in FIG. 5. FIG. 6 is a cross-sectional TEM image of the Y2O3 film of Example 1, and it was found that the Y2O3 film of Example 1 is composed of Y2O3 crystallites of about 5 nm to 10 nm, similar to the X-ray diffraction analysis result. From the TEM image shown in FIG. 6, it is recognized that the crystallites in most of the dense layer have a size of less than 10 nm. It was confirmed that the crystallites of 3 nm to 12 nm form a dense layer with a thickness of about 50 nm, and this dense layer forms a laminated structure, and the thickness (total film thickness) of the laminated structure is 1.4 μm (FIG. 6). At this time, the layers of the laminated structure are connected by dense layers of the same composition, and flat voids are generated between the laminated structures in the direction parallel to the substrate, but it was confirmed that the dense layers are extremely densely formed with tiny crystallites. When Au electrodes were attached to the surface of the obtained Y2O3 film and the electrical properties in the film thickness direction were measured, it was found to be a good insulating film with a withstand voltage exceeding 1.81 kV and a dielectric breakdown field strength of 12.7 MV / cm, which are extremely high values.
[0059] Example 2 The process from application of the Y2O3 ink C1 for forming an insulating film to laser irradiation in Example 1 was repeated 10 times, resulting in a Y2O3 film with a thickness of 0.87 μm. The obtained Y2O3 film was a good insulating film with a withstand voltage of 1.09 kV and a dielectric breakdown field strength of 12.5 MV / cm, both of which were extremely high values.
[0060] Example 3 The process from application of the Y2O3 ink C1 for forming an insulating film to laser irradiation in Example 1 was repeated five times, resulting in a Y2O3 film with a thickness of 0.37 μm. The obtained Y2O3 film was a good insulating film with a withstand voltage of 0.28 kV and a dielectric breakdown field strength of 7.37 MV / cm.
[0061] Example 4 In the KrF laser irradiation of Example 3, the second stage irradiation fluence was 80 mJ / cm 2 to 40 mJ / cm 2 When the dielectric strength was changed to 0.10 kV, a good insulating film with a dielectric breakdown field strength of 2.64 MV / cm was obtained.
[0062] Example 5 In the KrF laser irradiation of Example 3, the second stage irradiation fluence was 80 mJ / cm 2 to 60 mJ / cm 2 When the dielectric strength was changed to 0.21 kV, a good insulating film with a dielectric breakdown field strength of 5.48 MV / cm was obtained.
[0063] Example 6 In the KrF laser irradiation of Example 3, the second stage irradiation fluence was 80 mJ / cm 2 to 100 mJ / cm 2 When the dielectric strength was changed to 0.24 kV, a good insulating film with a dielectric breakdown field strength of 6.46 MV / cm was obtained.
[0064] When the X-ray diffraction patterns of the Y2O3 films obtained in Examples 2 to 6 were examined, very broad X-ray diffraction peaks were confirmed in all cases, and the crystallite diameters were analyzed to be 3 nm to 10 nm from the peak analysis.
[0065] Comparative Example 1 In the process of preparing the Y2O3 ink C1 for forming an insulating film in Example 1, the coarse aggregated particles were not removed, and a Y2O3 ink C2 for forming an insulating film was prepared containing aggregated particles of 100 nm or more. The Y2O3 ink C2 for forming an insulating film was used to form a film in the same process as in Example 3, and a Y2O3 film with a thickness of 0.77 μm was obtained. The withstand voltage of the obtained Y2O3 film was 0.12 kV, and the dielectric breakdown field strength was only 1.17 MV / cm, and a good insulating film was not obtained. At this time, the structure in the Y2O3 film was such that the connections of the layered structure were destroyed due to the inclusion of coarse particles.
[0066] Comparative Example 2 In the process of preparing the Y2O3 ink C1 for forming an insulating film in Example 1, a Y2O3 ink C3 for forming an insulating film that does not contain a yttrium 2-ethylhexanoate solution was prepared, and a film was formed using the Y2O3 ink C3 for forming an insulating film in the same process as in Example 3, resulting in a Y2O3 film with a thickness of 0.72 μm. The withstand voltage of the obtained Y2O3 film was only 0.004 kV, and the dielectric breakdown field strength was only 0.06 MV / cm, and a good insulating film was not obtained. At this time, large cracks occurred in the structure in the Y2O3 film, and a layer structure effective as an insulating film could not be formed.
[0067] Comparative Example 3 Solution C4 was prepared by diluting yttrium 2-ethylhexanoate solution twice with toluene without containing Y2O3 nanoparticles, and film formation was carried out using solution C4 in the same process as in Example 3. As a result, a Y2O3 film with a film thickness of 1.87 μm was obtained. The withstand voltage of the obtained Y2O3 film was only 0.145 kV, and the dielectric breakdown field strength was only 0.78 MV / cm, and a good insulating film was not obtained. At this time, large cracks occurred in the structure in the Y2O3 film, and a layer structure effective as an insulating film could not be formed.
[0068] Comparative Example 4 The step control irradiation in Example 1 was not performed, and the final irradiation power was set to 1.5 × 10 6 W s / cm 2 When pulsed light was irradiated only with the Y2O3 film, surface degradation occurred due to ablation, and the resistance value could not be reduced sufficiently.
[0069] Comparative Example 5 When the process from application of the Y2O3 ink C1 for forming an insulating film to laser irradiation in Example 1 was repeated twice, a Y2O3 film with a thickness of 0.16 μm was obtained. Although the dielectric breakdown field strength of the obtained Y2O3 film was 6.46 MV / cm in some places, there was a large variation depending on the measurement point, and stability of the characteristics could not be ensured at this thinness.
[0070] Comparative Example 6 The Y2O3 ink C1 for insulating film formation was spin-coated on an alumina substrate with Au sputtered at a rotation speed of 3000 rpm for 20 seconds to form a precursor film, and the precursor film after coating was pre-baked at 150°C for 5 minutes and 400°C for 10 minutes. The process from coating the Y2O3 ink C1 for insulating film formation to laser irradiation was then repeated a total of five times. After that, it was baked at 900°C for 1 hour, and the X-ray diffraction peak of the resulting insulating film increased, increasing its crystallinity (see Figure 5), and the crystallite diameter was calculated to be 17 nm. At this time, the dielectric breakdown field strength was 0.606 MV / cm, and the withstand voltage was only 0.022 kV. [Industrial Applicability]
[0071] According to the present invention, it is possible to obtain an insulating film having a superior thickness in the range of 300 nm to 20 μm. The present invention includes an insulating film forming ink for coating an insulating film, an insulating film having a laminated structure capable of realizing a withstand voltage of 1 kV or more or a dielectric breakdown field strength of 2.6 MV / cm or more, and a method for forming an insulating film capable of forming an effective insulating film using the insulating film forming ink. If a high withstand voltage or high dielectric breakdown field strength can be obtained in this film thickness range, it is expected that it will be possible to construct a highly reliable semiconductor manufacturing device and to manufacture a highly safe power electronics device, high voltage transistor, power conversion device, etc. In particular, in high voltage capacitors and high voltage switching devices, a high dielectric breakdown field strength exerts sufficient insulation while minimizing the thickness, and has a great advantage in miniaturizing devices, etc. In addition, since a coating type manufacturing method is realized, it is also possible to obtain a great cost advantage.
Claims
1. An insulating film forming ink comprising a solvent, an organometallic compound or a metal alkoxide, and oxide nanoparticles, the organometallic compound or the metal alkoxide contains a metal component constituting an insulating oxide material, the oxide nanoparticles are composed of crystallites of the insulating oxide material having a crystallite size of 0.5 nm or more and 15 nm or less; The oxide nanoparticles have an average primary particle diameter of 30 nm or less, The content of the oxide nanoparticles is 0.5% by mass or more and 10% by mass or less, The ink for forming an insulating film, wherein the content of the organometallic compound or the metal alkoxide is 5% by mass or more and 25% by mass or less.
2. Further comprising a nanoparticle dispersant, 2. The ink for forming an insulating film according to claim 1, wherein the content of the nanoparticle dispersant is 10% by mass or less.
3. The oxide nanoparticles are represented by the general formula AO x 2. The ink for forming an insulating film according to claim 1, comprising a compound represented by the formula: (wherein A is one or more elements selected from Sc, Y, group 3 elements of lanthanoids, Ti, Zr, group 4 elements of Hf, Nb, Ta, Si, and Al, and x is a value that matches the valence of A and maintains electrical neutrality, but allows for slight oxygen non-stoichiometry).
4. The organometallic compound or the metal alkoxide has the general formula M m R n (wherein M is one or more elements selected from Sc, Y, Group 3 elements of lanthanoids, Ti, Zr, Group 4 elements of Hf, Nb, Ta, Si, and Al; R is at least one selected from an alkyl group having 1 to 4 carbon atoms, a carboxyl group having 1 to 4 carbon atoms, and a carbonyl group; and m and n are integers), or a β-diketonate, or a long-chain alkoxide having 6 or more carbon atoms.
5. 2. The ink for forming an insulating film according to claim 1, wherein when the organometallic compound or the metal alkoxide is an organometallic compound, the solvent is a mixed solvent of b vol % aromatic hydrocarbon and 100-b vol % alcohol (10<b<90).
6. 2. The ink for forming an insulating film according to claim 1, wherein the organometallic compound or the metal alkoxide is a 2-ethylhexanoate.
7. 6. The ink for forming an insulating film according to claim 5, wherein the aromatic hydrocarbon is toluene or xylene.
8. 6. The ink for forming an insulating film according to claim 5, wherein the alcohol is 1-butanol or isopropanol.
9. The ink for forming an insulating film according to claim 3 , wherein A is Y.
10. The ink for forming an insulating film according to claim 4 , wherein the M is Y.
11. Y formed on the substrate 2 O 3 (A.O. x : A=Y, x=1.5), A laminated structure in which a plurality of dense layers each having a thickness of 30 nm or more and 300 nm or less are laminated, and the thickness of the laminated structure is 300 nm or more and 20 μm or less, The dense layer is 2 O 3 The crystallite size of the crystallite is 0.5 nm or more and 15 nm or less, The layers of the laminated structure are connected by layers of the dense layer having the same composition, An insulating film having a withstand voltage of 1 kV or more or a dielectric breakdown field strength of 2.6 MV / cm or more.
12. A first step of applying the ink for forming an insulating film according to any one of claims 1 to 10 onto a substrate to form a precursor film on the substrate; a second step of drying the precursor film at a temperature of 100° C. or more and 400° C. or less; a third step of irradiating the dried precursor film with a solid pulse laser having a wavelength of 266 nm or more and 355 nm or less, an excimer laser having a wavelength of 193 nm or more and 308 nm or less, or a flash lamp to form an insulating film.
13. The first step, the second step, and the third step are repeated in this order to obtain Y 2 O 3 (A.O. x 13. The method for producing an insulating film according to claim 12, wherein a laminate structure is formed in which a plurality of dense layers each having a thickness of 30 nm to 300 nm are laminated, the dense layers being composed of: A=Y, x=1.5).
Citation Information
Patent Citations
Sliding door unit with transom
JP1981097085A
Semiconductor or liquid crystal manufacturing device member and its manufacturing method
JP4006535B2
Method for producing crystallized metal oxide thin film
JP4258536B2
Thermistor manufacturing method
JP6529023B2